Revision of Engelimyia Lopes, 1975 (Diptera: Sarcophagidae) - Pape, Thomas; de Mello-Patiu, Cátia Antunes (Zootaxa, 2006)
The Neotropical genus Engelimyia Lopes, 1975 is revised and found to consist of four species: the already named E. bosqi (Blanchard, 1939) and E. inops (Walker, 1849), with the former nominal species herewith resurrected from synonymy with the latter; and two new species, E. qibos sp. nov. and E. psino sp. nov. A lectotype is designated for Sarcophaga cassidifera Engel, 1931 [= E. inops (Walker, 1849)]. Male terminalia of all species are illustrated, and a key to the species is provided. The four species appear to form two sister-group pairs: E. inops + E. psino and E. bosqi + E. qibos, both of which show a South American—Central American Isthmian disjunction, which here is considered to reflect the same vicariance event and a maximum age of the four species of about 3 My.